Keterampilan Dasar Guru Abad ke-21: Kunci Menuju Pembelajaran Kreatif dan Kolaboratif - Istiqomah Istiqomah; Rina Apriana; Cyndy Felisya; Sani Safitri; Rani Oktapiani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the basic skills of 21st-century teachers that play a role in creating creative and collaborative learning. Technological developments, changes in student characteristics, and modern educational demands place teachers in the role of facilitators who must master critical thinking, creativity, communication, collaboration, and the ability to integrate technology into the learning process. The results of the study show that mastery of these skills can increase student activity, motivation, and interaction, while also encouraging problem-solving and cooperation skills. In addition to pedagogical aspects, teachers' psychological readiness and attitudes toward the use of technology, including artificial intelligence, also influence the effectiveness of its application in the classroom. This study emphasizes the importance of continuous training, the development of relevant learning media, and institutional support so that teachers can adapt to the changes of the digital era. Thus, the basic skills of 21st-century teachers are an important foundation in realizing innovative and relevant learning for the needs of students.